Control, logística y aprovisionamiento de bienes, servicios e infraestructura en la Universidad Regional Autónoma de los Andes - Álvarez Chisaquinga, Fernando Xavier (2025)
The main purpose of this scientific article is to make a diagnosis to determine the management of the supply of goods and services at the Universidad Regional Autónoma de Los Andes is an institution of higher education located in the city of Ambato, km 51/2 via Baños, whose purpose is to train professionals of third and fourth level. According to the type of research it was classified as applied, quantitative transversal type. The population and sample was reported by 50 people through surveys. Direct observation of documents related to the Property, Financial and Warehouse Departments was also used. Finally, face-to-face interviews were conducted with the Directors and Heads of Property, Finance and Warehouse. The data obtained were processed using the Excel package. The results obtained showed that there is a lack of management and control in Procurement, being necessary to strengthen the areas with the creation of a Purchasing Committee that has the competence and authority to guide the processes in a technical manner. In conclusion, this research provides a scientific contribution for the companies of the country, offering a proposal for a significant improvement in the processes of procurement and control of goods and services.